A nation-wide survey of patients with homozygous familial hypercholesterolemia phenotype undergoing LDL-apheresis in Turkey (A-HIT 1 registry). (March 2018) - Kayikcioglu, Meral; Tokgozoglu, Lale; Yilmaz, Mehmet; Kaynar, Leylagul; Aktan, Melih; Durmuş, Rana Berru; Gokce, Cumali; Temizhan, Ahmet; Ozcebe, Osman Ilhami; Akyol, Tulay Karaagac; Okutan, Harika; Sag, Saim; et al.
Abstract: Background and aims: Homozygous familial hypercholesterolemia (HoFH) is a genetic condition characterized by lethally high levels of low-density lipoprotein cholesterol (LDL-C) from birth, and requires rapid and aggressive intervention to prevent death due to coronary heart disease and/or atherosclerosis. Where available, lipoprotein apheresis (LA) is the mainstay of treatment to promote survival. Methods: A-HIT1 registry was conducted with the aim of providing insight to the real-life management of HoFH patients undergoing LA in Turkey, where LA procedures are fully reimbursed and widely available. Participating centers provided patient information, including family history, treatment patterns and relevant laboratory values, via a standard questionnaire. Results: The study evaluated 88 patients (mean age: 27 ± 11 years, 41 women) in 19 centers. All patients were receiving regular LA with a clinical diagnosis of HoFH. Mean age at first symptom disease was 10 ± 10 years, and at diagnosis it was 12 ± 11 years; 74.7% were diagnosed before age 15 years; and only 31% before the age of 7. First referral of most patients was to pediatricians. Early onset coronary artery disease was present in 57.8% of patients. Mean age at first LA was 21 ± 12 years. Only 11 (12.5%) patients were undergoing LA weekly. Mean frequency of apheresis sessions was 19 ± 13 days. For the last four LA sessions, LDL-C levels reached the target in only in 5.7% of patients. Conclusions: Diagnosis of HoFH is delayed, and LDL targets are not reached. LA frequencies are not optimal. Urgent attention is needed to support the survival of patients with HoFH. Highlights: HoFH is a life threatening genetic condition of elevated LDL-C. Patients require rapid and aggressive intervention to enable survival. Patients with HoFH experience delayed diagnosis and sub-optimal treatment.